CULTIVATION SEED (Mystus nemurus C.V) USING BIOFILTER TAIWANESE CLAM ON AQUAPONIC SYSTEM - Ayu Kurnia Pitaloka; Usman M Tang; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted for 45 days from March to April 2013, inLaboratory Breeding Unit of the Faculty of Fisheries and Marine SciencesUniversity of Riau. The aim of the study was to determine the growth and rate ofseed (Mystus nemurus CV) using a biofilter taiwanese clam (Anadonta woodianaLea) on aquaponic system. The method used in this study was experimen with 1factor and 3 treatments. The treatments were stocking density of 5, 10, and 15taiwanese clam (Anadonta woodiana Lea) of each treatment.The results showed that stocking density taiwanese clam has significantlyaffect on the water quality of ammonia, nitrate, nitrite, growth rate and survivalrate of seed. The best result was achived by treatment P3 (15 tawanese clam).Total absolute growth weight was 16.63 grams, 2.20% daily growth rate andsurvival rate of 81.67%.Keywords: Aquaponik, Biofilter, Taiwanese Clam, Mystus nemurus CV